An Examination of the American Far Right's Anti-Tax Financial Crimes. (December 2019) - Sullivan, Brandon A.; Freilich, Joshua D.; Chermak, Steven M.
Little attention has been paid to ideologically motivated tax protesters who use frivolous legal arguments as moral or legal justification for committing tax fraud and related financial crimes. These crimes have defrauded private citizens and governments and are associated with violent far-right extremism, negatively impacting public safety and stability. Using data from the U.S. Extremist Financial Crime Database, we provide an exploratory, descriptive analysis of the composition and motivation of financial crime schemes associated with the American far-right extremist anti-tax movement. Our innovative open-source database permits systematic empirical research into connections among tax avoidance, anti-tax, and anti-government belief and related criminal behavior, which is necessary for the advancement of scholarship on the causes and consequences of these frauds and the development of sound intervention and prevention policies and practices.